Capture, amplification, and global profiling of microRNAs from low quantities of whole cell lysate. Issue 17 (2nd August 2017) - Wang, Nayi; Cheng, Jijun; Fan, Rong; Lu, Jun
Abstract : MicroRNAs (miRNAs) are small non-coding RNAs that control gene expression at the post-transcriptional level via a complex regulatory network that requires genome-wide miRNA profiling to dissect. Abstract : MicroRNAs (miRNAs) are small non-coding RNAs that control gene expression at the post-transcriptional level via a complex regulatory network that requires genome-wide miRNA profiling to dissect. The patterns of miRNA expression at the genome scale are rich in diagnostic and prognostic information for human diseases such as cancers. This analysis, however, requires multi-step purification of RNAs from large quantities of cells, which is not only time consuming and costly but also challenging in situations where cell numbers are limited. In this study, we report direct capture, amplification, and library preparation of miRNAs from whole cell lysate without the need of pre-purification. As a result, it enables genome-wide miRNA profiling reproducibly with low quantity of cell samples (∼500 hematopoietic cells). Specifically, we conducted a systematic investigation of two key steps – cell lysis for miRNA release and 3′ adaptor ligation required for direct miRNA capture and amplification. The obtained expression profile not only distinguishes cell types but also detects individual miRNA alterations in closely related isogenic cell lines. This approach, which is substantially simple as compared to the standard methods because of elimination of the need for RNA purification, is advantageous for the measurement of low quantity samples.